Kolaborasi BPBD dengan Masyarakat dalam Kebijakan Mitigasi Bencana Berbasis Komunitas FPRB Desa Tamanayu, Lumajang - Muhammad Amrul; Ika Devy Pramudiana; Sapto Pramono (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study examines the collaboration between the Regional Disaster Management Agency (BPBD) and community organizations, specifically the Forum for Disaster Risk Reduction (FPRB), in implementing community-based disaster mitigation policies in Tamanayu Village, Lumajang. Using a qualitative case study approach, the research explores the dynamics, processes, challenges, and successes of collaborative efforts in disaster risk reduction (DRR) at the local level. The analysis highlights the significance of participatory strategies, local knowledge, and community empowerment in enhancing disaster preparedness and resilience. The involvement of multiple stakeholders—including government, community members, academia, private sector, and media—underpins the practice of the Pentahelix concept, fostering an integrated approach to disaster mitigation. The findings reveal that effective collaboration depends heavily on mutual trust, shared understanding, and a robust institutional framework that embeds disaster mitigation within the social fabric of the community. Challenges identified include coordination issues, limited resources, bureaucratic barriers, and disparities in perception and capacity among stakeholders. Despite these obstacles, the community's proactive measures, such as self-organized simulations and local resource utilization, demonstrate increasing resilience and capacity. The study underscores the importance of strengthening local institutional support, continuous capacity building, and the integration of indigenous knowledge to ensure the sustainability of disaster mitigation efforts. Furthermore, strategic alignment and synchronization between BPBD's top-down policies and bottom-up community initiatives are crucial for effective implementation. The research provides valuable insights into how participatory governance and community empowerment can lead to more resilient societies capable of adapting to evolving risks, including climate-change impacts.